2018
DOI: 10.1093/jxb/ery017
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR164b-resistant OsNAC2 improves plant architecture and grain yield in rice

Abstract: Plant architecture affects grain yield. Overexpressing a version of OsNAC2 resistant to miRNA-mediated degradation increased panicle number and grain yield under field conditions, identifying a new strategy to improve yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 47 publications
3
50
0
Order By: Relevance
“…For example, the transgenic lines had a higher filling rate than that of the wild type plants under drought and heat stress conditions, resulting in increases in the total grain weight. These results were in consistent with that of previous studies which reported higher rice grain yield in rice plants overexpressing AP37 [66], TIFY [67], OsNAC2 [68], and OsNRT2.1 [69].…”
Section: Resultssupporting
confidence: 93%
“…For example, the transgenic lines had a higher filling rate than that of the wild type plants under drought and heat stress conditions, resulting in increases in the total grain weight. These results were in consistent with that of previous studies which reported higher rice grain yield in rice plants overexpressing AP37 [66], TIFY [67], OsNAC2 [68], and OsNRT2.1 [69].…”
Section: Resultssupporting
confidence: 93%
“…For example, overexpressing miR444b.1 negatively regulates rice blast resistance with reduced tiller numbers (Xiao et al, 2017), whereas, overexpression of its target gene OsMADS57 resulted in increased number of tillers (Guo et al, 2013). Similarly, miR164a negatively regulates M. oryzae resistance by suppressing OsNAC60 (Wang et al, 2018), whereas overexpression of another miR164 target, OsNAC2 , leads to improvement of plant architecture and grain yield in rice (Jiang et al, 2018). In these reports, immunity and yield traits were regulated by different miRNA isoforms or different target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation of miR398 can increase panicle length, grain number and grain size (Zhang et al ., 2017a) and suppressing expression of miR159 affects multiple traits of rice including grain shape by up‐regulating its targets OsGAMYB and OsGAMYBL1 (Zhao et al ., ). Overexpression of miR164b‐resistant target, OsNAC2, could make better plant architecture, longer panicles, more grain number and yield (Jiang et al ., ). However, so far there is little information showing the effect of miRNA on rice yield through affecting grain filling by negatively regulating its target.…”
Section: Introductionmentioning
confidence: 97%